2009
DOI: 10.1111/j.1440-1843.2009.01510.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of obstructive sleep apnoea in Samoa progressively reduces daytime blood pressure over 6 months

Abstract: Hypertensive OSA patients can exhibit large falls in BP with CPAP at 1 month, with further significant reductions at 3 and 6 months. Overall, the fall in BP was proportional to the initial elevation of the BP with many patients achieving normal BP at 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
6
1
1
Order By: Relevance
“…That is, patients who used ASV for longer each night were not more likely to experience cardiovascular death than those with lower usage levels. This is in contrast to findings from trials of PAP in patients with obstructive sleep apnoea where a dose–response effect for PAP has been reported, both for cardiovascular responses [ 30 ] and symptoms [ 31 ]; this was not seen for the negative effects of ASV on mortality in this analysis. However, the lack of dose dependency may have been a result of the way usage times were measured.…”
Section: Discussioncontrasting
confidence: 99%
“…That is, patients who used ASV for longer each night were not more likely to experience cardiovascular death than those with lower usage levels. This is in contrast to findings from trials of PAP in patients with obstructive sleep apnoea where a dose–response effect for PAP has been reported, both for cardiovascular responses [ 30 ] and symptoms [ 31 ]; this was not seen for the negative effects of ASV on mortality in this analysis. However, the lack of dose dependency may have been a result of the way usage times were measured.…”
Section: Discussioncontrasting
confidence: 99%
“…The current study extends previous work 1, 35 by demonstrating that the sole predictor of a reduction in both SBP and DBP with PAP was the presence of uncontrolled hypertension at baseline. Although PAP level was also a significant independent predictor of the reduction in DBP, the magnitude of this trend was not strong (β values indicated that each 1 cm H 2 O increase in PAP was associated with a reduction in DBP of < 1 mm Hg).…”
Section: Discussionsupporting
confidence: 88%
“…65% of our baseline patients were available for follow-up. This rate is in the range to be expected for CPAP follow-up [39][40][41]. In the recent study by JAVAHERI et al [13], 50% of patients with In order to address this issue, interventional studies on the effect of artificially improved (e.g.…”
Section: Initial Compsamentioning
confidence: 99%